2021
DOI: 10.3390/jcm10112491
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COPD on the Hospital Outcomes and Mortality among Hemorrhagic Stroke Patients. Sex Differences in a Population-Based Study

Abstract: (1) Background: It is not well known whether there is an association between COPD and hemorrhagic stroke (HS). We aim to analyze the incidence, clinical characteristics, procedures, and outcomes of HS in patients with and without COPD and to assess sex differences. Secondly, to identify factors associated with in-hospital mortality (IHM). (2) Methods: Patients aged ≥40 years hospitalized with HS included in the Spanish National Hospital Discharge Database (2016–2018) were analyzed. Propensity score matching (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Prior studies have been performed on this registry for other illnesses, including infectious diseases. They have recognised its high value for producing estimates of current burden and time trends for different clinical conditions at the national level 12–15 . Given that the Spanish health system provides universal coverage, even for illegal migrants, biases due to difficulties in access to care should be negligible.…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies have been performed on this registry for other illnesses, including infectious diseases. They have recognised its high value for producing estimates of current burden and time trends for different clinical conditions at the national level 12–15 . Given that the Spanish health system provides universal coverage, even for illegal migrants, biases due to difficulties in access to care should be negligible.…”
Section: Methodsmentioning
confidence: 99%
“…When the COPD-stroke mortality correlation was divided into short-term and long-term, we found that the evidence for the correlation of COPD effects on the short-term risk of death in stroke was not very strong, Studies by Lekoubou and Ovbiagele, [10] Szylińska et al, [9] and de Miguel-Diez et al [16] did not support this correlation, and they concluded that COPD has a limited effect on early stroke mortality. In contrast, COPD appears to have a progressive effect on stroke mortality as time prolongs.…”
Section: Discussionmentioning
confidence: 89%
“…Of the 27 included papers, 14 reported the risk of stroke in combination with COPD, [3,5,[16][17][18][19][20][21][22][23][24][25] 6 reported the risk of stroke in combination with AECOPD. [19,[26][27][28][29][30] The risk of death after stroke was reported in 12 articles.…”
Section: Basic Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations